Factors affecting employee's performance among private sector workers: a case study in Selangor / Tengku Nurul Baiti Najwa Tengku Rosli - Tengku Rosli, Tengku Nurul Baiti Najwa (Faculty of Business Management, 2017)
With the emerging new market, competitive among firms especially big firm seem to be increased from time to time. To retain competitive advantage, many firm willing to pay higher payment to the good employees who able to help them achieve their company goals. In a recent survey conducted by Job Street stated that Malaysia and Singapore fall in second and last ranking of country having higher job dissatisfaction due to poor leadership or management, poor training, and lack career development (W, 2016). Thus, money not everything in creates job satisfaction among employees. Through the survey also, the respondent from Singapore have expressed that job satisfaction can enhance job performance by getting a new job with 30% respondents who support it, having higher payment (19%) and having reward and recognition (9%).However, all of this factors cannot be said the only factors that contribute towards employee's performance. There are many factors that affect employee's performance at workplace. The factors include empowerment, transformational leadership, work environment and teamwork. Thus, this study was conducted to study the relationship between empowerment, transformational leadership, work environment, teamwork and employee's performance. The population in this study is the employees who work in area Selangor whereas the sample for the population that wants to be investigated are private sector employees only. 150 sets of questionnaires were prepared and distributed to the targeted respondents in a few area in Selangor. Then, SPSS software was used to generate the data to get the final result using multiple regression analysis to test the effect of independent variables (empowerment, transformational leadership, work environment and teamwork) towards employee's performance. Finding indicates that variables empowerment and teamwork having significant relationship towards employee's performance whereas transformational leadership and work environment having no significant relationship towards employee's performance.